2019
DOI: 10.1001/jamacardio.2019.2467
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, Care Patterns, and Outcomes of Patients Admitted to Cardiac Intensive Care Units

Abstract: ; for the Critical Care Cardiology Trials Network IMPORTANCE Single-center and claims-based studies have described substantial changes in the landscape of care in the cardiac intensive care unit (CICU). Professional societies have recommended research to guide evidence-based CICU redesigns. OBJECTIVE To characterize patients admitted to contemporary, advanced CICUs. DESIGN, SETTING, AND PARTICIPANTS This study established the Critical Care Cardiology Trials Network (CCCTN), an investigator-initiated multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 177 publications
(46 citation statements)
references
References 19 publications
1
37
0
8
Order By: Relevance
“…The over-qualification of care and the overuse of resources has also been documented in a recent US report. 19 Level 1 ICCU mismatches included the admission of patients with high illness severity to low-level ICCUs, which might be clinically more relevant. One explanation is the absence of high-level ICCUs in the studied hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The over-qualification of care and the overuse of resources has also been documented in a recent US report. 19 Level 1 ICCU mismatches included the admission of patients with high illness severity to low-level ICCUs, which might be clinically more relevant. One explanation is the absence of high-level ICCUs in the studied hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of contemporary North American tertiary and quaternary CICUs showed that HF is the second most common reason for admission after ACS but represents the longest LOS and most frequent indication for CICU therapies. 19 Moreover, HF was the second leading cause of CICU mortality, with an incidence of 12.0%. In a large retrospective analysis of 3.2 million HF hospitalizations in the United States between 2005 and 2015, all of which were patients 65 years and older, Wadhera et al.…”
Section: Discussionmentioning
confidence: 99%
“…El factor de riesgo cardiovascular más prevalente en los pacientes fue la hipertensión arterial seguido de la diabetes mellitus tipo 2, patrón semejante a reportes internacionales. 5,13,16 La presencia de comorbilidades como enfermedades pulmonares obstructivas crónicas (EPOC) e insuficiencia renal crónica se encuentra por debajo de los niveles reportados en registros europeos 5,15 mientras que los antecedentes cardiovasculares más frecuentes fueron enfermedad coronaria y falla cardíaca crónica similar a lo reportado por Gagliardi et al 18 Aunque se ha registrado un cambio epidemiológico en los pacientes admitidos en las UCIC a nivel mundial, el síndrome coronario agudo, principalmente con elevación del segmento ST, sigue siendo la primera causa de admisión a las unidades críticas cardíacas lo que se refleja en nuestra población (28.6%) semejante a lo ocurrido en los registros italiano, alemán, argentino y norteamericano (63.8%, 43.6%, 24.9% y 31.8% respectivamente) [14][15][16]18 .…”
Section: Discussionunclassified
“…La mortalidad en la UCC reportada en diversos registros varía entre 3.3 y 27.8% 5,[14][15][16]19 La mortalidad por falla cardíaca agudamente descompensada, la segunda causa de admisión a UCIC INCOR, fue similar a la observada en registros mencionados. 5,14,19 El grupo de mayor riesgo fue aquel que ingresó a UCIC proveniente de UCIN y hospitalización, los que presentaron una alta tasa de mortalidad (12.5%) la cual duplica la mortalidad de UCIC; este hallazgo no ha sido reportado por otros registros.…”
Section: Discussionunclassified